Sickle cell Anemia with avascular necrosis of femur being managed as rheumatic fever - Lamsal, KS (Journal of Institute of Medicine Nepal, 2013)
Sickle cell anemia is a rare hematological problem in Nepal and described only in the forms of case reports. This is a case report of a patient of sickle cell disease from Nawalparasi district of Nepal. The patient had history of recurrent joint pain including both large and small joints. He also had soft systolic murmur in cardiac auscultation for which he had received penicillin prophylaxis three years for clinically suspected rheumatic heart disease. He was later diagnosed to have Sickle cell anemia with avascular necrosis of right femoral head and functional murmur of severe anemia with no evidence of rheumatic heart disease. DOI: http://dx.doi.org/10.3126/joim.v34i1.9121 Journal of Institute of Medicine, April, 2012; 34:1 37-39